Pengaruh Jenis Adsorben Pada Proses Bleaching di Pemurnian Crude Palm Oil (CPO) Sebagai Bahan Baku Pada Proses Green Fuel - AZZAHRA, SYIFA FAJRINA; YOHANINGSIH, NING TYAS; KURNIAWAN, RONNY (e-Proceeding FTI, 2024)
Green fuel technology is a technology for producing green fuel by engineering products to produce green diesel, green aviation fuel and green gasoline. The raw material used in green fuel technology is vegetable oil from palm (CPO) which meets the specified specifications. To obtain the specifications for this vegetable oil, it must go through a purification process, including degumming and bleaching processes using tamarind seed adsorbents and zeolite. The purpose of this study was to determine the effect of the type of adsorbent on the bleaching process using tamarind seed adsorbents and zeolite with a mesh size of 170/200 and to determine the quality of the purified CPO to be compared with standard CPO feed to the green fuel process. Based on the research results of the bleaching process using organic (tamarind seed) and inorganic (zeolite) adsorbents with a mesh size of 170/200, CPO purified has a reddish-orange color, water content (0.24-0.29)%, fatty acids free (ALB) (0.19-0.27)%, acid number (0.41-0.45)mgKOH/gr. Abstrak Teknologi green fuel adalah teknologi produksi bahan bakar hijau dengan merekayasa produk sehingga menghasilkan green diesel, green avtur dan green gasoline. Bahan baku yang digunakan pada teknologi green fuel yaitu minyak nabati dari sawit (CPO) yang sudah memenuhi spesifikasi yang ditentukan. Untuk mendapatkan spesifikasi minyak nabati tersebut harus melalui proses pemurnian antara lain dengan proses degumming dan bleaching menggunakan adsorben biji asam jawa dan zeolit. Tujuan pada penelitian ini yaitu mengetahui pengaruh jenis adsorben pada proses bleaching dengan menggunakan adsorben biji asam jawa dan zeolit dengan ukuran mesh 170/200 serta mengetahui kualitas CPO hasil pemurnian tersebut untuk dibandingkan dengan standar CPO umpan ke proses green fuel. Berdasarkan hasil penelitian proses bleaching dengan menggunakan jenis adsorben organik (biji asam jawa) dan anorganik (zeolit) dengan ukuran mesh 170/200, CPO hasil pemurnian memiliki warna jingga kemerahan, kadar air (0,24-0,29)%, Asam lemak bebas (ALB) (0,19-0,27)%, bilangan asam (0,41- 0,45)mgKOH/gr.